Development of a biophyte-type hydrophytic structure for phytoremediation purpose - Mikhyeyev, O.M.; Lapan, O.V.; Madzhd, S.M.; Cherniak, L.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
A floating structure of a bioplateau has been developed for the purification of water bodies from the toxic substances, the biotic component of which is terrestrial plants. Chemically inert floating materials were used as a substrate for the construction of the bioplateau: perlite, expanded clay, granular foam, vermiculite, cork. Substrate testing has shown that granular expanded polystyrene is the most optimal for the usage. The study of different options for seed germination in the design of the bioplateau has shown that its placement on the top of the substrate is the best optionTo optimize the hydrophytic structure a grid was used, which made it possible to increase the overall density of the bioplateau. There was done a comparative study of the effectiveness of purification of the aquatic environment from ions of radiocesium bioplate with wheat plants of different varieties. It is confirmed that the efficiency of sorption of 137Cs ions by terrestrial plants is influenced by the nature and concentration of macrocations in the aqueous medium.